The Conflict Between Overtourism and Sustainable Tourism: A Comparative Analysis of Algeria and Spain Under Environmental and Social Pressures - Bouchagour, DR. Abdelkader; Guendouz, DR. Khaled Ben el walid; Mecelti, DR. Soufyane; Harizi, DR. Mokhfi (Journal of Ecohumanism, 2025)
This study aims to analyze the relationship between tourism development and environmental sustainability in Algeria and Spain in light of the growing environmental and social pressures on tourist destinations. It is based on the assumption that the Spanish experience—having witnessed high levels of environmental and social pressure as a result of overtourism—represents a model from which Algeria can benefit in order to avoid following the same trajectory during the development of its tourism sector. The research adopts a descriptive–analytical comparative approach, relying on international data and a critical review of specialized literature. The findings show that achieving sustainability in Algerian tourism requires open, participatory, and transparent governance, the development of mechanisms for regular monitoring of pressures on natural resources and local populations, as well as the adoption of proactive, data-driven policies, thereby ensuring a balance between economic growth, environmental protection, and quality of life.